Predictors of shared book reading at home with preschoolers: Are there differences between Roma and non-Roma low-income families? - Ferreira, I. (2021)
Previous research highlights several benefits of shared book reading (SBR) for child development, but less studies exist about its predictors (Yarosz & Barnett, 2001). Literature on home SBR in Portugal is scarce (Araújo & Costa, 2015; Peixoto et al., 2008), and studies on its predictors in families at socioeconomic risk or Roma families in this context are, respectively, reduced (Gamelas et al., 2003) or inexistent. This study aimed to investigate the predictors of the frequency of SBR in two ethnically diverse groups of families. Specifically, we studied the associations between child and family (mother) characteristics, parental aspirations, and parental involvement in preschool events and frequency of home SBR. Two hundred and six caregivers of Portuguese Roma ( n = 101) and non-Roma ( n = 105) low-income preschoolers (109 boys; M age = 5, SD age = 0.94) living in the Metropolitan areas of Lisbon and Oporto, Portugal, completed a survey, in face-to-face meetings. A multiple regression model, using AMOS (v. 25), showed that mothers’ educational level, educational aspirations for their child, and involvement in informal (but not formal) events in preschool were positively associated with frequency of SBR. Ethnicity did not moderate these associations. The overall similar pattern results for Roma and non-Roma low income families is an important finding, suggesting that these families may experience similar challenges in engaging in SBR with their preschool children and, therefore, may benefit from interventions with similar features.